Protection from illegal fishing and shark recovery restructures mesopredatory fish communities on a coral reef. Issue 18 (20th August 2019) - Speed, Conrad W.; Rees, Matthew J.; Cure, Katherine; Vaughan, Brigit; Meekan, Mark G.
Abstract: The recovery of communities of predatory fishes within a no‐take marine reserve after the eradication of illegal fishing provides an opportunity to examine the role of sharks and other large‐bodied mesopredatory fishes in structuring reef fish communities. We used baited remote underwater video stations to investigate whether an increase in sharks was associated with a change in structure of the mesopredatory fish community at Ashmore Reef, Western Australia. We found an almost fourfold increase in shark abundance in reef habitat from 0.64 hr −1  ± 0.15 SE in 2004, when Ashmore Reef was being fished illegally, to 2.45 hr −1  ± 0.37 in 2016, after eight years of full‐time enforcement of the reserve. Shark recovery in reef habitat was accompanied by a two and a half‐fold decline in the abundance of small mesopredatory fishes (≤50 cm TL) (14.00 hr −1  ± 3.79 to 5.6 hr −1  ± 1.20) and a concomitant increase in large mesopredatory fishes (≥100 cm TL) from 1.82 hr −1  ± 0.48 to 4.27 hr −1  ± 0.93. In contrast, near‐reef habitats showed an increase in abundance of large mesopredatory fishes between years (2.00 hr −1  ± 0.65 to 4.56 hr −1  ± 1.11), although only smaller increases in sharks (0.67 hr −1  ± 0.25 to 1.22 hr −1  ± 0.34) and smaller mesopredatory fishes. Although the abundance of most mesopredatory groups increased with recovery from fishing, we suggest that the large decline of small mesopredatory fish in reef habitat was mostly due to higher predation pressure following the increase in sharks and large mesopredatory fishes. At the regional scale, the structure of fished communities at Ashmore Reef in 2004 resembled those of present day Scott Reefs, where fishing still continues today. In 2016, Ashmore fish communities resembled those of the Rowley Shoals, which have been protected from fishing for decades. Abstract : We observed abundance and community composition of shark and mesopredatory reef fish at Ashmore Reef in Western Australia, before and after recovery from illegal fishing pressure. After eight years of recovery, there was a large decrease in small (≤50 cm TL) mesopredatory reef fish abundance and a concomitant increase in shark and large (>100 cm TL) mesopredatory fish abundance in reef habitat. Our findings provide support for fish community restructuring with reef shark recovery, which has implications for management time frames of marine protected areas.